2016
DOI: 10.1016/j.wneu.2016.07.068
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic Xanthoastrocytoma with Anaplastic Features: Retrospective Case Series

Abstract: aPXA is associated with poorer clinical outcomes compared with PXA. Gross total resection should be the goal of initial treatment. It remains unclear whether adjuvant radiation and chemotherapy are able to prevent progression or dissemination. Long-term monitoring of all patients is a critical step in management due to the potential for tumors to transform into higher-grade lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…In contrast, only 2 PXA cases showed heterogeneous enhancement, and 3 cases had marked peritumoral edema. The enhancement pattern of APXA could be explained by the presence of necrosis, hemorrhage, and vascular proliferation within the tumor, which was observed in most APXAs by Rutkowski et al 11 Additionally, our cohort showed results similar to those in a previous study for the frequency of the peritumoral edema. 20 In the study of Lim et al, 20 all PXAs with anaplastic features (4 cases) had severe perilesional edema, while only 1 of 18 PXAs presented with severe peritumoral edema, 6 cases had none, 8 cases had mild edema, and 3 cases had moderate edema.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, only 2 PXA cases showed heterogeneous enhancement, and 3 cases had marked peritumoral edema. The enhancement pattern of APXA could be explained by the presence of necrosis, hemorrhage, and vascular proliferation within the tumor, which was observed in most APXAs by Rutkowski et al 11 Additionally, our cohort showed results similar to those in a previous study for the frequency of the peritumoral edema. 20 In the study of Lim et al, 20 all PXAs with anaplastic features (4 cases) had severe perilesional edema, while only 1 of 18 PXAs presented with severe peritumoral edema, 6 cases had none, 8 cases had mild edema, and 3 cases had moderate edema.…”
Section: Discussionsupporting
confidence: 88%
“…5,10 Furthermore, APXA has been reported to have a worse prognosis than PXA, with 5-year overall survival of 57.1%. 5,11 Therefore, preoperative differentiation between the 2 entities by MR imaging may aid in planning the treatment strategy and predicting prognosis.…”
mentioning
confidence: 99%
“…eGBM and PXA exhibit some common findings on MRI: (i) contrast‐enhanced solid and/or cystic; (ii) well circumscribed with no or little peritumoral edema; (iii) leptomeningeal involvement; and (iv) leptomeningeal dissemination compared with diffuse glioma at recurrence . In our case series, one eGBM (case 15, Figs ) totally excised at first operation has been alive for over 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…The 3‐year progression‐free survival (PFS) was 32% for aPXAs compared with 80% for grade II PXAs. Another retrospective series of eight patients with aPXA demonstrated a 1‐year PFS of 57% . In this cohort, six patients had subtotal resections and all progressed despite adjuvant radiation and chemotherapy.…”
mentioning
confidence: 76%